2018
DOI: 10.1155/2018/2139626
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment of Written Phrasal Constructs and Grammar of Deaf and Hard of Hearing Students with Varying Expressive Language Abilities

Abstract: The purpose of this study was to examine the written phrasal constructs and grammar usage of deaf and hard of hearing students with varying expressive language skills. Twenty-nine d/hh middle school students attending a residential school for the deaf were divided into three language groups: students using spoken English, ASL/English bilinguals, and language delayed learners. Personal narrative writing samples were collected at the beginning, middle, and end of the academic year. The samples were divided into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Student's literacy development may be an equally difficult process especially for students with intricate linguistic histories. On the other hand, D/HH students exhibit strong proficiencies in literacy areas at par with hearing peers, particularly in written expression discourse and phonological cognizance (Bowers et. al/, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Student's literacy development may be an equally difficult process especially for students with intricate linguistic histories. On the other hand, D/HH students exhibit strong proficiencies in literacy areas at par with hearing peers, particularly in written expression discourse and phonological cognizance (Bowers et. al/, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…SIWI also incorporates "the language zone," an interactive, meaning-focused space where deaf students who struggle to communicate their ideas in language can use multimodal resources-including gestures, role play, images, and videos-to make themselves understood [166]. Research has shown that SIWI helps students to do all of the following: write longer pieces with more complex syntax; improve their writing skills across multiple genres; transfer writing strategies across genres; develop positive writer identities; gain writing independence; improve their editing and revising skills; and develop their ASL skills [167][168][169][170][171][172][173][174][175].…”
Section: Bimodal Bi/multilingual Writing Instructionmentioning
confidence: 99%
“…There are many different criteria that impact developmental language. Children who are DHH may experience language delays or language deprivation, which can influence how they are able to participate in assessments (Bowers, Dostal, Wolbers, & Graham, ; Marshall & Morgan, ; Meinzen‐Derr, Wiley, Phillips, Altaye, & Choo, ). Children who are DHH may be viewed as cognitively behind their peers due to this language delay (Miller, Thomas‐Presswood, Metz, & Lukomski, ).…”
Section: Impacts On Developmental Languagementioning
confidence: 99%